Unlocking deep relaxation: the power of rhythmic breathing on brain rhythms - Vaibhav Tripathi; Lakshmi Bhaskar; Chhaya Kharya; Manvir Bhatia; Vinod Kochupillai (npj Mental Health Research)
Abstract The pandemic has exacerbated mental health issues across the world. The limited availability of mental health professionals is preventing many from seeking help, which highlights the need for easily available mental health care routines like yoga, breathing, and meditation. A breath-based meditation technique known as Sudarshan Kriya Yoga (SKY) harnesses the power of breath to induce deep relaxation and makes meditation easier for beginners and has proven beneficial across multiple conditions, including depression, anxiety, and hypertension. The exact EEG dynamics happening during the practice are not well understood. We collected EEG data from 43 subjects undergoing SKY and analyzed their brain rhythms before, after, and during various stages of the technique, and found that rhythmic breathing accentuates theta rhythms (d = 0.63) which allows for an easier transition to a relaxed meditative state predominant with delta-theta rhythms, reduced alpha power (d = 1.70) and aperiodic signals (d = 2.04).